Co-creating a sustainability performance assessment tool for public sector organisations. (20th October 2021) - Ramos, Tomás B.; Domingues, Ana Rita; Caeiro, Sandra; Cartaxo, Joana; Painho, Marco; Antunes, Paula; Santos, Rui; Videira, Nuno; Walker, Richard M.; Huisingh, Donald
Abstract: Organisations are increasingly being pushed to manage, assess and report their sustainability performance, including public sector organisations (PSO). Several approaches were developed to implement sustainability assessments at the organisation level. However, the majority are still for the private sector and are often not supported by active stakeholder involvement. Several PSO have adapted private-oriented models to assess their sustainability performance, which are often not adequate due to public administration, whose main mission is to provide public services. The present work aims at developing a conceptual framework to support PSO and to assess their sustainability performance. The proposed approach is supported by two sustainability performance assessment systems – Formal and Informal Sustainability Performance Assessment . The Formal Sustainability Performance Assessment system, which is the main focus of this paper, consists of a checklist of objectives and practices and a set of twenty-nine (29) performance indicators. An initial proposal was drawn from the literature review and then assessed through a participatory process involving practitioners and academics in semi-structured interviews, questionnaire surveys and a collaborative workshop. The Portuguese central public administration was used as a case study. The developed checklist of objectives and practices and related performance indicators will allow PSO to assess and communicate complex information about organisational sustainability. Reference values support the normalization of indicators' results, and consequently, the comparison of sustainability-related performance between PSO integrated into the context of the Portuguese central public administration. This research contributes to the debate on organisational sustainability assessment and communication, and the importance of selecting and developing sustainability indicators using co-creation processes with key stakeholders. Graphical abstract: Image 1 Highlights: A framework for sustainability assessment of public organisations was co-created. The framework includes two sustainability assessment systems: Formal and Informal. A co-creation process involving practitioners and academic was adopted. The Portuguese central public administration was used as a case study. A checklist of objectives and practices and a set of 29 indicators were obtained.